Streptolysin O Deficiency in Streptococcus pyogenes M1T1 covR/S Mutant Strain Attenuates Virulence in In Vitro and In Vivo Infection Models - Emma L. Langshaw; Simone Reynolds; Victoria Ozberk; Jessica Dooley; Ainslie Calcutt; Mehfuz Zaman; Mark J. Walker; Michael R. Batzloff; Mark R. Davies; Michael F. Good; Manisha Pandey (mBio, 2023)
ABSTRACT Mutation within the Streptococcus pyogenes (Streptococcus group A; Strep A) covR/S regulatory system has been associated with a hypervirulent phenotype resulting from the upregulation of several virulence factors, including the pore-forming toxin, streptolysin O (SLO). In this study, we utilized a range of covR/S mutants, including M1T1 clonal strains (5448 and a covS mutant generated through mouse passage designated 5448AP), to investigate the contribution of SLO to the pathogenesis of covR/S mutant Strep A disease. Up-regulation of slo in 5448AP resulted in increased SLO-mediated hemolysis, decreased dendritic cell (DC) viability post coculture with Strep A, and increased production of tumor necrosis factor (TNF) and monocyte chemoattractant protein 1 (MCP-1) by DCs. Mouse passage of an isogenic 5448 slo-deletion mutant resulted in recovery of several covR/S mutants within the 5448Δslo background. Passage also introduced mutations in non-covR/S genes, but these were considered to have no impact on virulence. Although slo-deficient mutants exhibited the characteristic covR/S-controlled virulence factor upregulation, these mutants caused increased DC viability with reduced inflammatory cytokine production by infected DCs. In vivo, slo expression correlated with decreased DC numbers in infected murine skin and significant bacteremia by 3 days postinfection, with severe pathology at the infection site. Conversely, the absence of slo in the infecting strain (covR/S mutant or wild-type) resulted in detection of DCs in the skin and attenuated virulence in a murine model of pyoderma. slo-sufficient and -deficient covR/S mutants were susceptible to immune clearance mediated by a combination vaccine consisting of a conserved M protein peptide and a peptide from the CXC chemokine protease SpyCEP. IMPORTANCE Streptococcus pyogenes is responsible for significant numbers of invasive and noninvasive infections which cause significant morbidity and mortality globally. Strep A isolates with mutations in the covR/S system display greater propensity to cause severe invasive diseases, which are responsible for more than 163,000 deaths each year. This is due to the upregulation of virulence factors, including the pore-forming toxin streptolysin O. Utilizing covR/S and slo-knockout mutants, we investigated the role of SLO in virulence. We found that SLO alters interactions with host cell populations and increases Strep A viability at sterile sites of the host, such as the blood, and that its absence results in significantly less virulence. This work underscores the importance of SLO in Strep A virulence while highlighting the complex nature of Strep A pathogenesis. This improved insight into host-pathogen interactions will enable a better understanding of host immune evasion mechanisms and inform streptococcal vaccine development programs.